Metallic corrosion processes and information from corrosion products - Carvalho, LDC (Wiley, 2023)
Metallic corrosion can be defined as the natural process of deterioration of metals as they interact with the surrounding environment, usually in the presence of water. This chapter provides an overview of corrosion processes of the most common metals found in archaeological sites, the type of information that can currently be retrieved from corrosion products, and some common techniques for their analysis. Electrochemical corrosion involves the transfer of electrons from one location another with the help of a conductor. Corrosion may cover the whole object or only part of it, protect the metallic surface or disfigure it with craters or growths. The presence of corrosion is sometimes perceived as an obstacle to the study of archaeological metal objects because it obscures the metallic surface of objects. The bulk of corrosion products found on archaeological metal objects are formed as a result of the object's interaction with the deposition environment.